(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study addressed some of Ibn Jinni’s linguistic opinions, which appeared contradictory and inconsistent. We find some researchers mentioning one of these opinions, citing it as an argument, thinking that it was Ibn Jinni’s only opinion on this issue. Then, another researcher comes and mentions another opinion, and one thinks that Ibn Jinni contradicted himself in these two opinions on the same issue.The study tackled these opinions according to laws that Ibn Jinni had established to address what appeared to be contradictory for scholars preceding. He explained the reasons for the difference between the two opinions and how to know the opinion adopted by that scholar in a chapter he called (On the Two Expressions with the Same Meaning that are Reported from the Scholar as Contradictory). The study handled Ibn Jinni’s contradictory views through these laws and clarified which of the two views he favored. The study was limited to his views on general issues, such as the origin of languages, his position on Quranic readings, and his position on the grammatical factor, adopting an analytical, investigative approach. The study reached a set of results that can be summarized as follows. First, Ibn Jinni adopted different opinions on some issues and came with fatwas based on what he had in mind. Second, people may describe a scholar as contradictory based on certain foundations they rely on to judge between two opinions, but these foundations may not be correct, and they may imagine a contradiction, which in reality does not exist. Likewise, a scholar may attempt to develop his opinions and distance his opinions from those of his predecessors, and make an effort to innovate, but he remains in his teaching of his students and his writings on the approach of the prevailing schools of thought if he does not obtain sufficient conclusive evidence in his new field.